Pengaruh Peran Tour Leader Dalam Mendisiplinkan Rombongan Ibadah Jamaah Umrah Pada PT Sriwijaya Mega Wisata Tour Travel Palembang - Resi Purnama Sari; Candra Darmawan; Hasril Atieq Pohan (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT Thesis with the title "The Influence of the Tour Leader in Disciplining the Group Umrah Pilgrims at PT Sriwijaya Mega Wisata Tour and travel a tour Leaders are very necessary in facing obstacles in the field, one of which is regarding congregational discipline which includes awareness, obedience and obedience congregation to listen to directions from the Tour Leader who has a thesis spirit with the title "The Influence of the Tour Leader in Disciplining the Group."Umrah Pilgrims at PT Sriwijaya Mega Wisata Tour and travel a tour leaders are very necessary in facing obstacles in the field, one of which is regarding congregational discipline which includes awareness, obedience and obedience congregation to listen to directions from the Tour Leader who has a soul leadership, for example, in terms of time discipline, namely utilizing time well in carrying out the series of Umrah pilgrimage activities. This research aims to find out how much influence the tour leader has on discipline of PT Sriwijaya Mega Wisata Palembang Umrah pilgrims. This research using a type of quantitative research with survey techniques carried out by distributing questionnaires. The sample consisted of 55 people. Data analyzed with Instrument Testing, Assumption Testing, and Hypothesis Testing using toolshelp with SPSS version 26 software. The results of this study show that there is The influence of the tour leader on the discipline of the congregation, this has been proven The value of R square in the table is 0.114 which shows that the variable Congregation Discipline (Y) is influenced by the Tour Leader variable (X) by 11.4% and the remaining 88.6% was influenced by other factors not studied. leadership, for example, in terms of time discipline, namely utilizing time well in carrying out the series of Umrah pilgrimage activities. This research aims to find out how much influence the tour leader has on discipline of PT Sriwijaya Mega Wisata Palembang Umrah pilgrims. This research using a type of quantitative research with survey techniques carried out by distributing questionnaires. The sample consisted of 55 people. Data analyzed with Instrument Testing, Assumption Testing, and Hypothesis Testing using tools help with SPSS version 26 software. The results of this study show that there is The influence of the tour leader on the discipline of the congregation, this has been proven The value of R square in the table is 0.114 which shows that the variable Congregation Discipline (Y) is influenced by the Tour Leader variable (X) by 11.4% and the remaining 88.6% was influenced by other factors not studied. KEYWORDS: Promotion Strategy and Increase the Number Of Student